Anti-Currere - Wallin, Jason (Philosophical Inquiry in Education, 2025)
This article proposes anti-currere as a non-philosophical intervention in curriculum theory, drawing on the work of François Laruelle to challenge the field’s foundational obsession with the Real. It argues that curriculum study, despite its surface diversity, remains structurally wedded to a philosophical decision that monopolizes reality by predetermining what is thinkable. Through incisive critique of canonical concepts like the planned/lived curriculum binary, the paper reveals how curricular discourse habitually reproduces the very structures it claims to disrupt. In response, anti-currere is posited as a radical strategy of withdrawal from the decisional compulsions of the field – a minoritarian, non-standard mode of thought that reorients curriculum toward the immanence of the Real rather than its capture. Rather than offering another curriculum-as-x, anti-currere opens a space for stranger, generic curricular thought unbound by the auto-production of identity, representation, and method.